Training of clinical triage of acute radiation casualties: a performance comparison of on-site versus online training due to the covid-19 pandemic. (15th November 2021) - Lamkowski, Andreas; Combs, Stephanie E; Abend, Michael; Port, Matthias
Abstract: A collection of powerful diagnostic tools have been developed under the umbrellas of NATO for ionising radiation dose assessment (BAT, WinFRAT) and estimate of acute health effects in humans (WinFRAT, H-Module). We assembled a database of 191 ARS cases using the medical treatment protocols for radiation accident victims ( n = 167) and the system for evaluation and archiving of radiation accidents based on case histories ( n = 24) for training purposes of medical personnel. From 2016 to 2019, we trained 39 participants comprising MSc level radiobiology students in an on-site teaching class. Enforced by the covid-19 pandemic in 2020 for the first time, an online teaching of nine MSc radiobiology students replaced the on-site teaching. We found that: (a) limitations of correct diagnostic decision-making based on clinical signs and symptoms were experienced unrelated to the teaching format. (b) A significant performance decrease concerning online (first number in parenthesis) versus on-site teaching (reference and second number in parenthesis) was seen regarding the estimate time (31 vs 61 cases per hour, two-fold decrease, p = 0.005). Also, the accurate assessment of response categories (89.9% vs 96.9%, p = 0.001), ARS (92.4% vs 96.7%, p = 0.002) and hospitalisation (93.5% vs 97.0%, p = 0.002) decreased by around 3%–7%. The performances of the online attendees were mainly distributed within the lower quartile performance of on-site participants and the 25%–75% interquartile range increased 3–7-fold. (c) Comparison of dose estimates performed by training participants with hematologic acute radiation syndrome (HARS) severity mirrored the known limitations of dose alone as a surrogate parameter for HARS severity at doses less than 1.5 Gy, but demonstrated correct determination of HARS 2–4 and support for clinical decision making at dose estimates >1.5 Gy, regardless of teaching format. (d) Overall, one-third of the online participants showed substantial misapprehension and insecurities of elementary course content that did not occur after the on-site teaching.